2010
DOI: 10.1007/s13105-010-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber of “Rihane” barley grains and azoxymethane on serum and liver lipid variables in Wistar rats

Abstract: The aim of the present study is to evaluate the effects of diet enriched with dietary fiber of barley variety "Rihane" and azoxymethane on serum and liver lipid variables in male rats. Forty male rats were divided into four groups and fed on control diet or experimental diet that contained control enriched with dietary fiber of barley variety "Rihane". Animals were injected with saline (controls) or azoxymethane (20 mg/kg body weight s.c.) at 7 and 8 weeks of age. The experimental diet significantly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Dietary fibre (DF) plays a critical role in reducing blood TG, cholesterol and hepatic lipid contents and improvement in liver health (Guo et al., ; Lahouar et al., ). Thus, we examined the effects of DF on fat deposition in liver and relative mechanism of DF working for meat ducks from 1 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibre (DF) plays a critical role in reducing blood TG, cholesterol and hepatic lipid contents and improvement in liver health (Guo et al., ; Lahouar et al., ). Thus, we examined the effects of DF on fat deposition in liver and relative mechanism of DF working for meat ducks from 1 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that the dietary fibre (DF) could reduce blood TG and cholesterol, and hepatic lipid contents in rodent studies (van Bennekum, Nguyen, Schulthess, Hauser, & Phillips, ; Guo, Shu, & Yang, ; Lahouar et al., ). Similar results have also been reported in the chicken, where DF resulted in lower relative liver weight and/or fat mass (Akiba & Matsumoto, ; Mohiti‐Asli et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Recent experiments proved that TBV had considerable protective effects against both cardiovascular disease and colon cancer. [33,35] In the present work, we investigated the antimicrobial capacities of seed ethanolic extracts against five human pathogenic bacteria to search for novel biological activities for the TBV. Our findings (Fig.…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…Tunisia, Maroko, Algeria, Afganistan, Lebanon, Cyprus, China, Libya dan Iraq. Rihane adalah salah satu jenis kultivar barley lokal di negara Tunisia yang saat ini mulai banyak diteliti (Lahouar et al, 2011). Penelitian yang berkembang umumnya berkaitan dengan komposisi dan nilai fungsional barley terhadap kesehatan.…”
unclassified
“…Penelitian yang berkembang umumnya berkaitan dengan komposisi dan nilai fungsional barley terhadap kesehatan. Menurut Kalra et al (2000) (Lahouar et al, 2011;Kalra et al, 2000;Li et al, 2003) dan juga manusia secara langsung (Behall et al, 2004;Shimizu et al, 2008;Telati et al, 2009…”
unclassified